Temozolomide Plus Bevacizumab in Elderly Patients with Newly Diagnosed Glioblastoma and Poor Performance Status: An ANOCEF Phase II Trial (ATAG). (22nd February 2018) - Reyes‐Botero, Germán; Cartalat‐Carel, Stéphanie; Chinot, Olivier L.; Barrie, Maryline; Taillandier, Luc; Beauchesne, Patrick; Catry‐Thomas, Isabelle; Barrière, Jérôme; Guillamo, Jean‐Sebastien; Fabbro, Michel; Frappaz, Didier; Benouaich‐Amiel, Alexandra; et al.
Abstract : Lessons Learned : Results suggest that the combination of bevacizumab plus temozolomide is active in terms of response rate, survival, performance, quality of life, and cognition in elderly patients with glioblastoma multiforme with poor performance status. Whether this combination is superior to temozolomide alone remains to be demonstrated by a randomized study. Background: The optimal treatment of glioblastoma multiforme (GBM) in patients aged ≥70 years with a Karnofsky performance status (KPS) <70 is not established. This clinical trial evaluated the efficacy and safety of upfront temozolomide (TMZ) and bevacizumab (Bev) in patients aged ≥70 years and a KPS <70. Materials and Methods: Patients aged ≥70 years with a KPS <70 and biopsy‐proven GBM were eligible for this multicenter, prospective, nonrandomized, phase II trial of older patients with impaired performance status. Treatment consisted of TMZ administered at 130–150 mg/m 2 per day for 5 days every 4 weeks plus Bev administered at 10 mg/kg every 2 weeks. Results: The trial included 66 patients (median age of 76 years; median KPS of 60). The median overall survival (OS) was 23.9 weeks (95% confidence interval [CI], 19–27.6), and the median progression‐free survival (PFS) was 15.3 weeks (95% CI, 12.9–19.3). Twenty‐two (33%) patients became transiently capable of self‐care (i.e., KPS >70). Cognition and quality of life significantly improved over time during treatment. Grade ≥3 hematological adverse events occurred in 13 (20%) patients, high blood pressure in 16 (24%), venous thromboembolism in 3 (4.5%), cerebral hemorrhage in 2 (3%), and intestinal perforation in 2 (3%). Conclusion: This study suggests that TMZ + Bev treatment is active in elderly patients with GBM with low KPS and has an acceptable tolerance level.